The expression of glycolysis-related proteins in urine significantly increases after running - Zhao, Tian; Liu, Tianci; Li, Tao; Chen, Shengcun; Wang, Lupeng; Zhang, Man (Frontiers in Physiology, 2024)
ObjectiveGlucose metabolism is the main way in which cells obtain energy during exercise and plays an important role in exercise. The purpose of this study was to explore the changes in the expression of glucose metabolism-related proteins in urine after running, and finally applied to the monitoring of running training.MethodsUrine samples were collected before and after running, and urine proteomics information was collected to explore the expression of proteins in the urine using LC-MS/MS in DDA mode and DIA mode. Receiver operating characteristic (ROC) curve was drawn to evaluate the value of target proteins in monitoring running training.ResultsA total of 140 proteins were identified using LC-MS/MS in DDA mode, of which 49 urine proteins showed increased expression after running. KEGG analysis revealed that glucose metabolism-related proteins are mainly concentrated in glycolysis. There were six glycolysis-related proteins, among which urine proteins PKM, TPI1, ENO1 and LDHB were significantly increased after running (P < 0.05). This changes in urine proteins PKM, TPI1, ENO1 and LDHB were further verified by the results of LC-MS/MS in DIA mode. The concentrations of the urine proteins TPI1, ENO1 and LDHB showed a significant linear relationship with PKM. ROC curve analysis showed that PKM, TPI1, ENO1 and LDHB proteins in urine had good monitoring values for running training.ConclusionThe expression of glycolysis-related proteins PKM, TPI1, ENO1 and LDHB in urine was significantly increased after running, which may be applied to the monitoring of running training.